Metal-Rich Transition Metal Diborides as Electrocatalysts for Hydrogen Evolution Reactions in a Wide Range of pH. Issue 13 (1st January 2016) - Sitler, Steven J.; Raja, Krishnan S.; Charit, Indrajit
Abstract : Solid solutions of HfB2 -ZrB2 mixtures were prepared by high-energy ball milling of diboride and additive powders followed by spark plasma sintering (SPS). A mixture of stoichiometric 1:1 HfB2 -ZrB2 borides was the base composition to which Hf, Zr, Ta, LaB6 or Gd2 O3 was added. Hf, Zr and Ta were added in order to bring the boron-to-metal ratio down to 1.86, rendering the boride as MeB1.86 . In the case of LaB6 and Gd2 O3, 1.8 mol% was added. Electroanalytical behavior of hydrogen evolution reactions was evaluated in 1 M H2 SO4 and 1 M NaOH solutions. The LaB6 additive material showed Tafel slopes of 125 and 90 mV/decade in acidic and alkaline solutions respectively. The Hf and Zr rich samples showed Tafel slopes of about 120 mV/decade in both electrolytes. The overpotentials of hydrogen evolution reactions (at 10 mA/cm 2 ) in the alkaline solution were about 100 mV lower than those in acidic solution. The metal-rich diborides and addition of LaB6 showed better hydrogen evolution reaction (HER) activities than the base 1:1 HfB2 -ZrB2 stoichiometric diboride solid solution. The higher activity of metal-rich borides could be attributed to the increased electron population at the d -orbitals of the metal shown by band structure modeling calculations using the Density Functional Theory approach.